Contrastive Study of English with Arabic in Imperative Sentence - Farianti, Suci (The Explora, 2021)
The objectives of the research are to identify the differences and the similarities which can be found between imperative sentence in English and Arabic. The variable of this research is imperative sentence which is compared and contrasted to the English and Arabic language. In addition, in collecting the data, the writer uses library study and documentation technique. It is because the research was held in the library to find out the data from books, journals, and the other documents which are related to the research. Moreover, the writer also uses nothing technique and separating technique as the technique of analysis data. In describing the data, the writer also uses qualitative approach and descriptive analysis to interpret the data systematically and to find out the characteristic of imperative sentence in English and Arabic. Afterwards, to analyze the data the writer uses content analysis to analyze how far the data can describe and interpret the complete informations about the variable of the research in order to find out the similarities and the differences of imperative sentence in English and Arabic completely through contrastive analysis. Based on the result, imperative sentence in English and Arabic have the differences in several points such as the difference of the subject, the forms of the verb, the pattern, etc. However, there are also the similarities of imperative sentence in English and Arabic in general such as the similarity of the use ‘you’ as the subject, positive and negative imperative sentence as the form, etc.